Psychological Approach to the Competency Model of the Head of Department of Internal Affairs in the Context of Time Management - Vakhina V.V; Demin G.I; Ulyanina O.A (Moscow State University of Psychology and Education, 2017)
The paper reviews psychological rates of success and effectiveness in the work of heads and staff of Departments of Internal Affairs. Time management skills are especially important for police officers considering the specificity of their work. This study was aimed at exploring competencies of heads of Departments of Internal Affairs in terms of time management. The purpose of the study was to find out the main causes of the losses in the work time of heads of Departments of Internal Affairs; to explore the importance of optimizing time resources for achieving positive results in operational activities; to reveal the measures taken by managers to optimize the losses of official time. A questionnaire was used as a research method. 250 heads of police departments of various levels took part in the survey. The results obtained in the study enabled the authors to define the organizational and psychological bases for improving the use of time in workplace.